Effects of teachers school-level environment perceptions on changing elementary mathematics classroom environments - Blose, Ralph J. (Curtin University, 2003)
The purpose of this study was to establish an action research plan for teachers to improve student outcomes by assessing, describing, and changing their classroom environments. This study relied on student perceptions, using survey responses, to assess and describe the classroom environment. Teachers used this information to develop intervention strategies designed to change the students' perceptions of their actual classroom environment to more closely mirror their preferred classroom environment perceptions.More than forty years of classroom environment research has proven the importance of the classroom environment in developing positive student outcomes. Additional research has established the reliability of student perceptions of their learning environment. Previous research has developed several dependable student survey instruments to measure student perceptions of their classroom environment.This study was conducted in a Title I elementary school in the United States over a seven month period. Two intermediate level mathematics teachers participated in the project. Both quantitative data, using the My Classroom Inventory (MCI) and the School Level Environment Questionnaire (SLEQ), and qualitative data, teachers' case studies, were collected and analyzed.The study established that an action research plan for teachers to assess, describe, and change their classroom environments could be developed. However, even though teachers realized the benefits, for their students and themselves, in changing their classroom environments, school level environment demands negatively influenced their willingness to implement changes to their classroom environments.